(untitled) (REMUNOM, 2025)
One of the main reasons for the growth of the Brazilian ceramic industry is the large availability of natural raw materials found in the country. Therefore, the correct and appropriate selection of raw materials is of great importance. In this context, the present study aims to evaluate the potential of the rock powders — muscovite monzogranite, zoisite amphibolite, and limestone — in ceramic bodies used for tile manufacturing, analyzing their possible influence on the technological and microstructural properties of the final product. The raw materials were subjected to particle size distribution analysis, plasticity tests, chemical, mineralogical, and thermal characterization. The results obtained in this preliminary characterization stage indicate that the raw materials evaluated are technically promising for application in the ceramic industry. Keywords: raw materials; tiles; stones; ceramics.